Effect of one minute preceptor workshop on pediatrics residents' teaching skills - De Villa-Manlapaz, Ma. Luisa
Teaching medical students is an integral part of the Pediatrics residency training program. However, Pediatrics residents in St. Luke's Medical Center do not undergo any formal training in clinical teaching. This quasi-experimental study aimed to find out how teaching the One Minute Preceptor (OMP) to 3rd year Pediatrics residents of St. Luke's Medical Center affected their teaching skills as shown by their use of the five micro-skills. Pre-intervention encounters preceded The One Minute Preceptor seminar workshop. In these encounters, each resident discussed with two students an actual and a paper case of common pediatric conditions. These encounters were audio-recorded by the investigator. After each encounter, both the residents and the student participants answered a pre-validated OP rating scale. This consisted of 11 questions that tested the five micro-skills of the One Minute Preceptor. The intervention of this study consisted of a 2½ hour seminar workshop. It started with a lecture on the OMP. After the lecture, the residents were divided into small groups. Each group discussed a paper case which was provided by the investigator. Using the OMP, the participants alternately played the role of both teacher and students. A plenary session followed the small group discussion. In the plenary session, the five micro-skills, the three groups alternately played the roles of teachers and students. In this way, everyone was able to act as teachers and students and provide feedback to each other regarding the performance of the five micro-skills. Closures consisted of feedback from the participants regarding the seminar workshop and a summary by the investigator/lecturer. The post-intervention resident encounters occurred after the OMP seminar workshop. The resident-student post-intervention encounters followed the same format as that of the pre-intervention encounters. The primary measures included the change in the frequency of use of the five micro-skills by the residents after the intervention and the change in the resident and student rating of these skills after the intervention. The residents' self ratings showed significant increase in the skills' ?probing for supporting evidence? and ?giving feedback? and ?overall effectiveness.? On the other hand, the students' rating on the resident's performance did not show any change since they consistently gave the residents high ratings before and after the seminar workshop. There was an overall trend of improvement of residents' teaching skills. However, there was a significant improvement only in the use of the first microskill ?getting a commitment.? There was no significant increase in the use of the other microskills: proving for supporting evidence, teaching general rules, reinforcing what was done right and correcting mistakes. This study showed that the One Minute Preceptor seminar workshop resulted in an improvement, although limited, in the teaching skills of the third year Pediatrics residents. It is recommended that the training of OMP consist of more than one seminar workshop to reinforce the teaching of microskills and provide feedback to the learners. It is also recommended that the OMP be incorporated in the curriculum of the Pediatrics residency training program.